The Archaeology of Houses and Households in the Native Southeast - Steere, Benjamin A., 1981- (Book collections on Project MUSE., 2017)
The Archaeology of Houses and Households in the Native Southeast contributes enormously to the study of household archaeology and domestic architecture in the region. This significant volume combines both previously published and unpublished data on communities from the Southeast and is the first systematic attempt to understand the development of houses and households as interpreted through a theoretical framework developed from broad-ranging studies in cultural anthropology and archaeology. Steere's major achievement is the compilation of one of the largest and most detailed architectural datasets for the Southeast, including data for 1,258 domestic and public structures from 65 archaeological sites in North Carolina, Georgia, Alabama, Tennessee, Kentucky, and the southern parts of Missouri, Indiana, and Illinois. Rare data from hard-to-find cultural resource management reports is also incorporated, creating a broad temporal and geographic scope and serving as one of many remarkable features of the book, which is sure to be of considerable value to archaeologists and anthropologists interested in comparative studies of architecture. Similar to other analyses, Steere's research uses multiple theoretical angles and lines of evidence to answer archaeological questions about houses and the people who built them. However, unlike other examinations of household archaeology, this project spans multiple time periods (Woodland, Mississippian, and Historic); is focused squarely on the Southeast; features a more unified approach, using data from a single, uniform database; and privileges domestic architecture as a line of evidence for reconstructing daily life at major archaeological sites on a much broader scale than other investigations.